Uzbekistan Presidential Resolutions #5742 and #4919 shift subsidies from energy to water saving in lift irrigation schemes - CGIAR Research Program on Water, Land and Ecosystems (2020)
Shift in subsidies from energy to water saving technologies in lift irrigated areas.